Fortalecimiento del perfil profesional con la implementación del software contable “Mónica”, para los estudiantes de la Unidad Académica de Ciencias Administrativas y Humanísticas de la extensión La Maná año 2014 - Bastidas Peñafiel, María Elena (2014)
This research study aims at strengthening the professional profile of the students of the Academic Unit of Administrative Sciences and Humanities of the Technical University of Cotopaxi in Canton La Mana especially students of Engineering degree in Accounting and Auditing. The results of this investigation are summarized in a diagnosis applied to the academic part of the race in question, favorable conditions for the implementation of an accounting system as the linchpin of the race was determined, moreover academic opportunities offered by this such systems.